Antimicrobial activity and chemical characterization of the bark decoction of cumaru stem - Ferreira,Maria Jaiana Gomes (2020)
ABSTRACT: The plant, Amburana cearensis A. C. Smith (Fabaceae), commonly called cumaru, is widespread in the Caatinga cearense, a less known ecosystem in Brazil. A. cearensis is rich in several compounds like protocatechuic acid, tannins, coumarin, flavonoids and phenolic heterosides, such as amburosides A and B, that have been isolated. The aim of this study was to determine the antimicrobial potential and draw the chemical profile of the distinct characteristics of A. cearensis stem bark decoction, for its possible potential as a food conservation agent. The chemical compounds were characterized by one- and two-dimensional 1H and 13C NMR analyses and Liquid Chromatography-Mass Spectrometry (LCMS). The compounds of coumarin, amburosides A and B, and glycosylated (Z)-o-coumaric acid. Using the plaque microdilution technique, the antimicrobial action was tested on Escherichia coli, Salmonella Enteritidis, Pseudomonas aeruginosa, Staphylococcus aureus and Listeria monocytogenes. The decoction demonstrated antimicrobial activity on Gram-positive bacteria. This was encouraging because natural antimicrobials are beneficial for food production, as they can inhibit the pathogenic microorganisms and boost the quality of hygiene and cleanliness.